2020
DOI: 10.1016/j.transci.2020.102836
|View full text |Cite
|
Sign up to set email alerts
|

Management of blood supply and demand during the COVID-19 pandemic in King Abdullah Hospital, Bisha, Saudi Arabia

Abstract: Background: Maintaining blood supply is essential since blood transfusions are lifesaving in many conditions. The 2003 infectious outbreak of SARS-CoV had a negative impact on blood supply. This study aimed to measure donor attendance and blood demand in order to help find efficient ways of managing blood supply and demand during the COVID-19 pandemic and similar public emergencies in the future. Materials and methods: Data from donor attendance, mobile blood drives and blood inventory records were retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
2
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(94 citation statements)
references
References 18 publications
6
83
2
3
Order By: Relevance
“…However, this was with a concomitant 18.9% decrease in request. This value is lower than 39.5% reduction in donation and 21.7% reduction in request reported in Saudi Arabia [7] . There has been outcry of reduction in donor pool across the globe owing to the current pandemic [16] , [17] , [18] .…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…However, this was with a concomitant 18.9% decrease in request. This value is lower than 39.5% reduction in donation and 21.7% reduction in request reported in Saudi Arabia [7] . There has been outcry of reduction in donor pool across the globe owing to the current pandemic [16] , [17] , [18] .…”
Section: Discussioncontrasting
confidence: 60%
“…Nigeria confirmed its index case on February 27; a 44-year-old Italian who entered Nigeria on February 22 via Murtala Muhammed International Airport Lagos from Milan, Italy. [6] The pandemic has affected a good number of health services including blood donation [7] . Maintaining a steady stream of safe blood is very important as it plays vital role in medical and surgical procedures [8] .…”
Section: Introductionmentioning
confidence: 99%
“…They noted a significant drop of 39.5% in blood bank-based collections. At the same time, they also noted a drop in blood demand by 21.7% [3]. Wang et al reported a similar experience from The First Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou, China [4].…”
Section: Impact Of Social Distancing On Blood Donation Drivesmentioning
confidence: 80%
“…This has contributed to a significant drop in the number of blood drives and storage inventory. The phenomenon of the drop in voluntary donation has been noted in many countries across the globe [3,4]. Yahia et al recently published their eight months (from September 2019 to May 2020) experience with blood supply and demand in King Abdullah Hospital, Bisha, Saudi Arabia.…”
Section: Impact Of Social Distancing On Blood Donation Drivesmentioning
confidence: 99%
“…Improvisation of a disaster and infectious disease outbreak response team led by a transfusion medicine specialist is important to promptly develop mitigation guidelines and policy [ 18 ]. Less common measures available in other countries such as blood collection at donor’s home, establishment of rare donors’ registry, loosening donor’s eligibility criteria, extended donation hours, sharing of blood inventories with neighboring hospitals, could be considered in time of blood supply crisis [ 13 , 19 ].…”
Section: Blood Supply Management During the Covid-19 Pandemic: Experimentioning
confidence: 99%